DEBILITATING NEUROGLYCOPENIA SECONDARY TO HIRATA DISEASE ACHIEVING REMISSION SPONTANEOUSLY - RAS, Raja Azafirah; WA, Siti Sanaa; MA, Masliza Hanuni; Ashari, Nor Amani; Apparow, Saraswathy (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Insulin Autoimmune Syndrome (IAS), also known as Hirata’s disease, is a rare cause of hyperinsulinaemic hypoglycaemia. It is characterised by spontaneous hypoglycaemia associated with extremely high circulating insulin levels and positive anti-insulin antibodies. Hypoglycaemic episodes usually occur in the post-prandial state and are commonly associated with other autoimmune conditions, such as Graves’ disease, systemic lupus erythematosus and rheumatoid arthritis. CASE We report a case of a 62-year-old male with a background history of hypertension and cerebrovascular accident who presented with reduced consciousness. His capillary blood glucose levels ranged from 1.7 to 2.2 mmol/L and hypoglycaemia symptoms resolved following intravenous dextrose administration. The patient denied any consumption of oral hypoglycemic agents, exogenous insulin or traditional medications. Hypoglycaemia episodes occurred in both fasting and postprandial states. There was no weight gain to suggest insulinoma, and there were no constitutional symptoms to suggest underlying malignancy. No associated autoimmune conditions were noted. Systemic examination was unremarkable. Laboratory results revealed random blood glucose levels of 1.7 mmol/L, with marked elevation of insulin level of >6944 pmol/L and C-peptide level of 3496 pmol/L. Renal and liver profile and septic parameters were all within normal range. Insulin autoantibody (IAA) titers were elevated at 175 IU/mL (positive >20 IU/mL). Sulfonylurea levels were undetectable, and tumour markers were within normal limits. Localisation studies with CT, MRI and endoscopic ultrasound of the pancreas showed a normal pancreaticobiliary system. He was initially managed with oral prednisolone 10 mg twice daily and responded well. The dose was tapered off over two months with no recurrent episodes of hypoglycaemia afterwards. CONCLUSION IAS should be considered in a patient with postprandial hypoglycaemia with marked elevation of insulin levels. The diagnosis can be confirmed by elevation of insulin autoantibody titres. Most cases are self-remitting but may be managed with low-carbohydrate meals, steroids and steroid-sparing immunosuppressants.